Analysis of the Validity of Notarial Deeds in Land Ownership Transactions by Foreign Nationals through Nominees based on Law No. 5 of 1960 concerning Basic Agrarian Principles - Prakoso, Giesma Dwi; Nabila, Shafa Kintan; Samosir, Tetti (JURNAL AKTA, 2025)
Law No. 5 of 1960 concerning Basic Agrarian Regulations (UUPA) explicitly limits land ownership in Indonesia to Indonesian citizens (WNI). However, in practice, many foreign citizens (WNA) use the nominee scheme to acquire land by listing the name of the WNI as the formal owner in the land title certificate. This scheme is generally facilitated through a notarial deed containing a nominee agreement, absolute power of attorney, or a sale and purchase agreement. This study aims to analyze the validity of notarial deeds made in land ownership transactions by WNA through a nominee scheme based on applicable laws and regulations. The research method used is normative legal research with a statute approach and a case approach. The results of the study indicate that notarial deeds made in nominee transactions can be considered null and void because they conflict with the UUPA and the principle of legal certainty in the Indonesian agrarian system.  Based on Article 21 paragraph (1) and (3) of the UUPA, land ownership rights cannot be owned by foreign nationals, and if transferred to foreign nationals, the land must be released within one year or fall to the state. In addition, nominee agreements made before a notary also conflict with Article 1320 of the Civil Code because they have an “unlawful cause” (causa illicita). Therefore, stricter supervision of nominee practices and more assertive legal reform are needed to prevent misuse of this scheme and maintain agrarian sovereignty in Indonesia.